Correlation of Ahlback grading and knee society score in patients with moderate to severe osteoarthritis of the knee - Phalswal, Uma; Pandey, Vandna; Kumar, Ashok; Elhence, Abhay (International Journal of Research in Orthopaedics, 2021)
Background: Knee osteoarthritis (OA) is a most common rheumatological disorder that causes functional limitation and disability. The most common problem in knee OA are joint pain and stiffness. It will lead to decreased quality of life and it have a serious economic burden on any country due to effect of disability and treatment. Methods: A correlational study was conducted to find out correlation between Ahlback grading and knee society score (KSS) on a sample of 100 moderate to severe knee OA patients and 142 OA knees. Data was collected at orthopedics OPD, for a period of 3 months by purposive sampling. Results: On evaluation, mean age of the participants was 60.19±1.01. Out of 100 patients, 42 patients had bilateral knee OA, therefore total 142 knees included in the analysis. More than half (51%) participants were overweight. Only 34% subjects had compliament to physiotherapy. Around 76% subjects taking analgesics and massage therapy to reduce knee pain. Maximum 82.4% subjects had a poor knee condition in KSS and mean score is 49.07±1.06. Ahlback grading in X-ray had negative correlation -0.610 with KSS. Hence it is evaluated, both the scales have approximately same result as it is analyzed that both scales are moderately correlated. There is significant association of age, occupation and physiotherapy with Ahlback grading followed with KSS significant associated with BMI, occupation and physiotherapy. Conclusions: The study concluded that there is a moderate correlation found between Ahlback X-ray grading and knee society scoring. X-ray and knee society scoring (clinical evaluation) both are essential for effective treatment of OA.